Multi-purpose trigger system for medium particle detector devices - Clemêncio, Filomena (2021)
We report on an architecture of a multi-purpose trigger system based on inexpensive and off-the-shelf modules, with logic implemented in three levels, that can be used in a variety of small/medium systems just by writing a few registers using the accompanying software. The developed trigger algorithms are described in Very High Speed Integrated Circuits (VHSIC) Hardware Description Language (VHDL) and implemented using a Xilinx XC6LX45-2 FPGA. In its present implementation, for the sake of simplicity, communication with the external world is done using the Serial Peripheral Interface (SPI), which allows easy connection to a Raspberry Pi2 running Linux. The Raspberry software was written in C++ and enables configuring and checking of the underlying FPGA and retrieving the monitoring data. The system has been used, with success, in several applications, from lab setup to industrial and pre-clinical environments showing its versatility and robustness.